Comb-shaped polymer viscosity-reducing air entraining agent, its preparation method and application

CN122978362APending Publication Date: 2026-10-27ANHUI CONCH MATERIAL TECHNOLOGY CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610980591.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2026-06-30
Filing Date
2026-07-02
Publication Date
2026-10-27

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present application belongs to the technical field of concrete admixtures, and discloses a comb-shaped polymerization air entraining agent with viscosity reduction, a preparation method and application thereof. The air entraining agent is a comb-shaped anionic copolymer. Unsaturated carboxylic acid, unsaturated polyether macromonomer, unsaturated sulfonic acid monomer, unsaturated ester monomer and foam stabilizing monomer are synchronously grafted and polymerized through aqueous solution redox radical polymerization to form an integrated polymer molecule. The product has space steric hindrance viscosity reduction performance, and the three-dimensional network bubbles formed are stable. The foam stabilizing chain segment in the chain segment strengthens the film toughness. The product has the triple functions of efficient air entraining, viscosity reduction and long-acting foam stabilization, and has the advantages of low dosage and uniform and stable bubbles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of concrete admixture technology, specifically relating to a comb-type polymerized viscosity-reducing air-entraining agent, its preparation method, and its application. Background Technology

[0002] Air-entraining agents play a crucial role in the construction of concrete projects. By introducing uniform and stable micro-air bubbles into the concrete slurry, they improve the workability, freeze-thaw resistance, and impermeability of the concrete.

[0003] Traditional air-entraining agents are mostly single small molecules or oligomers such as rosin thermal polymers, alkylbenzene sulfonates, and fatty alcohol sulfates. Their air-entraining function is relatively simple, with no viscosity-reducing effect. Some anionic small-molecule air-entraining agents can exacerbate the formation of flocculation structures in cement paste, leading to excessively high paste viscosity. They are unsuitable for applications requiring low paste viscosity, such as high-grade concrete, manufactured sand concrete (manufactured sand has many sharp edges and high stone powder content), and self-compacting concrete.

[0004] In existing technologies, air-entraining agents and viscosity-reducing agents are often combined to achieve the dual effects of air entrainment and viscosity reduction. However, this method has significant drawbacks: First, the compatibility of the compounded components is poor, easily leading to stratification and precipitation; second, small-molecule compounded components are easily hydrolyzed and decomposed in the alkaline environment of cement paste, resulting in poor bubble stability and problems such as bubble coalescence and rupture. This leads to rapid loss of air content in concrete; third, the compounded product cannot achieve the synergistic effect of air-entraining and viscosity-reducing groups at the molecular structure level, resulting in low viscosity-reducing efficiency, high dosage, and increased cost. Summary of the Invention

[0005] The purpose of this invention is to provide a comb-type polymerized viscosity-reducing air-entraining agent and its preparation method.

[0006] Another objective of this invention is to provide an application of a comb-type polymerized viscosity-reducing air-entraining agent in concrete.

[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows:

[0008] This invention provides a method for preparing a comb-type polymerized viscosity-reducing air-entraining agent, the method comprising the following steps:

[0009] 1) Add deionized water to the reaction vessel and raise the temperature;

[0010] 2) Add unsaturated carboxylic acid monomer, unsaturated polyether macromonomer, and unsaturated sulfonic acid monomer to the reaction vessel and stir until completely dissolved;

[0011] 3) Add oxidizing and reducing agents dropwise to initiate a free radical reaction;

[0012] 4) After the reaction is complete, cool down and adjust the pH value to 6-7 to obtain the comb-type polymerized viscosity-reducing air-entraining agent.

[0013] In step 1), the temperature range for heating is 40~60℃.

[0014] In step 2), the unsaturated carboxylic acid monomer is one or more of methacrylic acid or acrylic acid.

[0015] In step 2), the unsaturated polyether macromonomer is one or more of isopentenyl polyoxyethylene ether or allyl polyoxyethylene ether, and the molecular weight of the unsaturated polyether macromonomer is 1000~3000.

[0016] In step 2), the unsaturated sulfonic acid monomer is one or more of sodium vinyl sulfonate or sodium methpropylene sulfonate.

[0017] In step 2), the mass ratio of the unsaturated carboxylic acid monomer, unsaturated polyether macromonomer, unsaturated sulfonic acid monomer, viscosity-reducing monomer, and foam-stabilizing monomer is 100~120∶420~480∶65~80∶0~50∶0~60.

[0018] According to a specific embodiment of the present invention, preferably, the oxidant is one or more of ammonium persulfate or potassium persulfate, and the reducing agent is sodium bisulfite; the mass ratio of the unsaturated polyether macromonomer, oxidant and reducing agent is 420-480:4-6:8-12.

[0019] In step 3), the reaction temperature of the free radical reaction is 40~60℃, including a dropwise reaction stage and a heat preservation reaction stage. The dropwise reaction stage lasts for 2~3 hours, and the heat preservation reaction stage lasts for 3~4 hours.

[0020] Furthermore, the preparation method of the comb-type polymerized viscosity-reducing air-entraining agent includes the following steps:

[0021] 1) Add deionized water to the reaction vessel and raise the temperature;

[0022] 2) Add unsaturated carboxylic acid monomer, unsaturated polyether macromonomer, unsaturated sulfonic acid monomer, viscosity reducing monomer and foam stabilizing functional monomer to the reaction vessel, and stir until completely dissolved;

[0023] 3) Add oxidizing and reducing agents dropwise to initiate a free radical reaction;

[0024] 4) After the reaction is complete, cool down and adjust the pH value to 6-7 to obtain the comb-type polymerized viscosity-reducing air-entraining agent;

[0025] The foam-stabilizing monomer is one or more of acrylamide or allyl dodecyl polyether; the viscosity-reducing monomer is one or more of methyl methacrylate, vinyl oleate, lauryl methacrylate or vinyl stearate.

[0026] This invention provides a comb-type polymerized viscosity-reducing air-entraining agent.

[0027] The comb-type polymerized viscosity-reducing air-entraining agent is a comb-type anionic copolymer prepared by free radical polymerization of aqueous solution. The main molecular chain is a carbon-carbon linear main chain, and the side chains are one or more of hydrophilic anionic air-entraining segments, polyether viscosity-reducing segments, ester viscosity-reducing segments, or hydrophobic alkyl stabilizing segments. The side chains are covalently grafted onto the main chain.

[0028] Specifically, the hydrophobic alkyl stabilizing segment is introduced by a foam-stabilizing functional monomer, the polyether viscosity-reducing segment is introduced by an unsaturated polyether macromonomer, the ester viscosity-reducing segment is introduced by a viscosity-reducing monomer, and the hydrophilic anionic gas-entraining segment is introduced by an unsaturated sulfonic acid monomer.

[0029] The molecular weight of the comb-type polymerized viscosity-reducing air-entraining agent is 30,000~50,000 g / mol.

[0030] The present invention also provides the application of the above-mentioned comb-type polymerized viscosity-reducing air-entraining agent in concrete.

[0031] The reaction mechanism of the air-entraining agent in this invention is an aqueous free radical graft polymerization reaction initiated by a redox system. The entire polymerization process is divided into four stages: chain initiation, chain propagation, chain transmission, and chain termination. The reaction is green and environmentally friendly, with mild reaction conditions and controllable degree of polymerization. The specific mechanism is as follows:

[0032] Chain initiation stage: A persulfate-sodium bisulfite redox initiation system is employed. Under mild conditions of 20-60℃, the initiator decomposes to generate primary free radicals; these radicals attack the carbon-carbon double bonds of the unsaturated functional monomers, breaking the double bond stability and forming monomeric active free radicals, providing active sites for subsequent chain growth. This initiation system operates at a mild reaction temperature, avoiding monomer decomposition due to high temperatures and effectively ensuring the integrity of the graft copolymerization of functional groups.

[0033] Chain growth and main chain formation stages: The active free radicals of unsaturated carboxylic acid monomers, unsaturated polyether macromonomers, and unsaturated alkyl sulfonic acid monomers sequentially add to form a linear carbon-carbon main chain. Anionic active sites such as carboxyl and sulfonic acid groups are uniformly distributed on the main chain, while side chain branching sites are retained. The molecular weight and arrangement of functional groups in the main chain are designed and adjusted by controlling the monomer dropping rate and reaction temperature to avoid excessively wide molecular weight distribution and disordered molecular structure, ensuring a uniform and stable molecular structure distribution.

[0034] Side-link grafting polymerization stage: The double bonds at the end groups of the polyether macromonomer undergo graft copolymerization with the active sites of the main chain, forming flexible polyether long side chains. Simultaneously, unsaturated sulfonic acid monomers are grafted, forming short-chain hydrophobic alkyl side chains and anionic sulfonic acid side chains. This stage is a simultaneous grafting polymerization, with the three types of side chains evenly distributed on the main chain, generating a comb-like polymer structure.

[0035] Chain termination stage: When the monomer conversion rate reaches over 98%, the free radical reaction is terminated, and the polymer molecular weight is controlled between 30,000 and 50,000 g / mol. This ensures that the molecular chain length is suitable for the cement paste environment. This avoids the problem of unstable air-entraining bubbles due to excessively small molecular weight of the air-entraining agent, while also avoiding the problem of poor solubility and excessive dosage caused by excessively large molecular weight of the air-entraining agent.

[0036] The product is prepared without physical mixing of free small molecules, exhibiting strong stability in the alkaline environment of cement and avoiding component separation issues. Functional synergy is achieved at the molecular structure level.

[0037] This invention relates to a polymeric air-entraining agent that, when added to concrete, leverages the unique structure of its comb-like polymeric molecular chains. Through the synergistic effect of the polymeric chain segments, it achieves both viscosity reduction and air entrainment functions. The mechanism of action is as follows:

[0038] The flexible polyether long side chains of the comb-type polymer are hydrophilic nonionic segments. Upon addition to the slurry, they rapidly adsorb onto the surface of cement particles and aggregates, forming a dense hydration film. On one hand, the long polyether segments create a steric hindrance effect, breaking down the flocculated and agglomerated structure between cement particles. This releases free water trapped within the flocculated structure, reducing frictional resistance within the slurry. On the other hand, the polyether segments have a lubricating effect, forming a molecular-level lubricating layer between the aggregates and cement particles, reducing sliding resistance between particles.

[0039] The sulfonic acid and carboxyl anionic groups on the main and side chains of the molecule dissociate to form negative charges in the slurry. These charges are adsorbed at the gas-liquid interface, reducing the surface tension of water and inducing uniform nucleation of microbubbles. Simultaneously, hydrophobic alkyl side chains extend into the bubble interior, and hydrophilic anionic segments extend into the aqueous phase, forming a stable double-layer bubble film. The long side chains of the comb-shaped polymer molecules intertwine and cross-link, forming a three-dimensional network polymeric protective structure on the bubble surface. This improves the strength and toughness of the bubble film, preventing bubble coalescence and rupture, and achieving stable and controllable air content in concrete. Compared to traditional small-molecule air-entraining agents, the bubble film formed by the polymer molecules is thicker and more stable, meeting the durability requirements of concrete.

[0040] The viscosity-reducing segment and the air-entraining segment are covalently linked to the same polymer backbone, and they are simultaneously adsorbed and act in the slurry without functional antagonism. The viscosity-reducing segment lowers the slurry viscosity, providing a loose slurry environment for the uniform dispersion of microbubbles and preventing the high-viscosity slurry from squeezing the bubbles and causing them to break. The microbubbles formed by the air-entraining segment further play a lubricating role, helping to reduce the slurry viscosity.

[0041] Compared with the prior art, the present invention has the following advantages:

[0042] 1. Through controlled polymerization, gas entrainment, viscosity reduction, and stabilizing group covalent bonding are achieved. The product is a single polymer with no free small molecules, excellent compatibility, and stable storage without stratification or precipitation. It can effectively solve the antagonistic problem of physical compounding. Through the dual effects of steric hindrance and lubrication of comb-type polymerization long chains, the viscosity reduction effect is significant, which can reduce the viscosity of concrete paste and make the concrete cavitation speed suitable for special systems such as manufactured sand concrete, high-grade concrete above C50, and self-compacting concrete.

[0043] 2. The stable three-dimensional network structure bubble film formed by polymer molecules has uniform bubble pore size and strong stability, which is far superior to the traditional air-entraining agent in Comparative Example 1;

[0044] 3. The reaction is a controlled free radical polymerization process in aqueous solution, with adjustable molecular weight and molecular structure, high batch stability of product performance, mild reaction conditions, no organic solvents, and meets the requirements for green building materials production;

[0045] 4. The air-entraining agent described in this invention has high functional efficiency, requires a lower dosage than traditional compound products, does not affect concrete strength, and reduces negative effects. Detailed Implementation

[0046] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0047] Unless otherwise specified, all test materials and reagents used in the following examples are commercially available.

[0048] Example 1

[0049] A method for preparing a comb-type polymerized viscosity-reducing air-entraining agent specifically includes the following steps:

[0050] 1) Add 600g of deionized water to the reactor and heat to 45℃;

[0051] 2) Add 120g of acrylic acid, 450g of allyl polyoxyethylene ether with a molecular weight of 2500 and 80g of sodium methacrylate and stir to dissolve.

[0052] 3) Add 5g of ammonium persulfate and 10g of sodium bisulfite as a mixed initiator, and add the mixture dropwise at 45℃ for 2.5h, then keep the mixture at this temperature for 3.5h.

[0053] 4) After cooling, adjust the pH value to 6.5 to obtain the comb-type polymerized viscosity-reducing air-entraining agent with a solid content of 50%.

[0054] Example 2

[0055] A method for preparing a comb-type polymerized viscosity-reducing air-entraining agent specifically includes the following steps:

[0056] 1) Add 600g of deionized water to the reactor and heat to 48℃;

[0057] 2) Add 100g methacrylic acid, 480g isopentenyl polyoxyethylene ether with a molecular weight of 2500 and 70g sodium vinyl sulfonate, and stir to dissolve;

[0058] 3) Add 4.5g of potassium persulfate and 9g of sodium bisulfite as a mixed initiator, add dropwise at 48℃ for 2 hours, and keep the reaction at this temperature for 3 hours;

[0059] 4) After cooling, adjust the pH value to 6.8 to obtain the comb-type polymerized viscosity-reducing air-entraining agent with a solid content of 50%.

[0060] Example 3

[0061] A method for preparing a comb-type polymerized viscosity-reducing air-entraining agent specifically includes the following steps:

[0062] 1) Add 600g of deionized water to the reactor and heat to 45℃;

[0063] 2) Add 110g of acrylic acid, 420g of allyl polyoxyethylene ether with a molecular weight of 2400 and 70g of sodium methacrylate sulfonate, then add 20g of methyl methacrylate, 20g of vinyl oleate and 50g of acrylamide dropwise, and stir until completely dissolved.

[0064] 3) Add 5.2g of ammonium persulfate and 10.4g of sodium bisulfite aqueous solution dropwise at 45℃ for 2.5h, and keep the reaction at this temperature for 3.5h.

[0065] 4) After cooling, adjust the pH value to 6.5 to obtain a comb-type polymerized viscosity-reducing air-entraining agent containing foam-stabilizing segments, with a solid content of 50%.

[0066] Example 4

[0067] A method for preparing a comb-type polymerized viscosity-reducing air-entraining agent specifically includes the following steps:

[0068] 1) Add 600g of deionized water to the reactor and heat to 45℃;

[0069] 2) Add 110g of acrylic acid, 420g of allyl polyoxyethylene ether with a molecular weight of 2400 and 70g of sodium methacrylate, then add 20g of methyl methacrylate, 20g of vinyl oleate and 50g of acrylamide and stir until completely dissolved.

[0070] 3) Add 5.2g of ammonium persulfate and 10.4g of sodium bisulfite as a mixed initiator, and add the mixture dropwise at 45℃ for 2.5h, then keep the mixture at this temperature for 3.5h.

[0071] 4) After cooling, adjust the pH value to 6.5 to obtain a comb-type polymerized viscosity-reducing air-entraining agent containing foam-stabilizing segments, with a solid content of 50%.

[0072] Example 5

[0073] A method for preparing a comb-type polymerized viscosity-reducing air-entraining agent specifically includes the following steps:

[0074] 1) Add 600g of deionized water to the reactor and heat to 45℃;

[0075] 2) Add 105g methacrylic acid, 420g isopentenyl polyoxyethylene ether with a molecular weight of 2500 and 65g sodium vinyl sulfonate, then add dropwise 30g lauryl methacrylate, 20g vinyl stearate and 60g allyl dodecyl polyether, and stir until completely dissolved.

[0076] 3) Add 4.8g of potassium persulfate and 9.6g of sodium bisulfite as a mixed initiator, add dropwise at 45℃ for 2 hours, and keep the reaction at this temperature for 3 hours;

[0077] 4) After cooling, adjust the pH value to 6.7 to obtain a comb-type polymerized viscosity-reducing air-entraining agent containing foam-stabilizing segments, with a solid content of 50%.

[0078] Example 6

[0079] A method for preparing a comb-type polymerized viscosity-reducing air-entraining agent specifically includes the following steps:

[0080] 1) Add 600g of deionized water to the reactor and heat to 45℃;

[0081] 2) Add 105g methacrylic acid, 420g isopentenyl polyoxyethylene ether with a molecular weight of 2500, 65g sodium vinyl sulfonate, 30g lauryl methacrylate, 20g vinyl stearate and 60g allyl dodecyl polyether, and stir until completely dissolved.

[0082] 3) Add 4.8g of potassium persulfate and 9.6g of sodium bisulfite as a mixed initiator, add dropwise at 45℃ for 2 hours, and keep the reaction at this temperature for 3 hours;

[0083] 4) After cooling, adjust the pH value to 6.7 to obtain a comb-type polymerized viscosity-reducing air-entraining agent containing foam-stabilizing segments, with a solid content of 50%.

[0084] Comparative Example 1

[0085] This comparative example is a compound of triterpenoid saponins and a commercial viscosity reducer, wherein the mass ratio of triterpenoid saponins to the commercial viscosity reducer is 1:10, and the commercial viscosity reducer is Qingdao Dingchang New Materials viscosity reducer.

[0086] Performance Testing and Result Analysis

[0087] The air-entraining agents prepared in Examples 1-6 were compounded with concrete at a dosage of 0.03%. The blank group consisted of C50 concrete without the air-entraining agent. Performance comparison experiments were conducted on the compounded concrete according to the "Standard for Test Methods of Performance of Ordinary Concrete Mixtures" GB / T50080-2016. The performance was evaluated based on the slump time of the concrete in an inverted slump cone; a shorter slump time indicated a better viscosity reduction effect. The air content of the concrete was also determined according to the same standard. The compressive strength of the concrete was tested according to the "Standard for Test Methods of Physical and Mechanical Properties of Concrete" GB / T50081-2019. The concrete mix design is shown in Table 1 below, and the performance test results are shown in Table 2 below.

[0088] Table 1. Mix Proportions for C50 Concrete

[0089]

[0090] Table 2. Performance test results of C50 concrete prepared using the air-entraining agents in Examples 1 to 6 and Comparative Example 1, respectively.

[0091] Table 2

[0092]

[0093] The test results show that, under the same concrete mix proportion, the air-expanding time of the concrete in Comparative Example 1 is 23.6s, while the concrete with the viscosity-reducing air-entraining agent has significantly better fluidity and shorter air-expanding time, without affecting the compressive strength of the concrete.

[0094] It should be noted that the above embodiments are merely some preferred embodiments of the present invention, and not all embodiments. Obviously, based on the above embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort should fall within the scope of protection of the present invention.

[0095] The above description of the embodiments is intended to enable those skilled in the art to understand and use the invention. It will be apparent to those skilled in the art that various modifications can be made to these embodiments, and the general principles described herein can be applied to other embodiments without inventive effort. Therefore, the present invention is not limited to the above embodiments, and any improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the invention should be within the protection scope of the present invention.

Claims

1. A method for preparing a comb-type polymerized viscosity-reducing air-entraining agent, characterized in that, The preparation method includes the following steps: 1) Add deionized water to the reaction vessel and raise the temperature; 2) Add unsaturated carboxylic acid monomer, unsaturated polyether macromonomer, and unsaturated sulfonic acid monomer to the reaction vessel and stir until completely dissolved; 3) Add oxidizing and reducing agents dropwise to initiate a free radical reaction; 4) After the reaction is complete, cool down and adjust the pH value to 6-7 to obtain the comb-type polymerized viscosity-reducing air-entraining agent.

2. The preparation method according to claim 1, characterized in that, In step 1), the temperature range for heating is 40~60℃.

3. The preparation method according to claim 1, characterized in that, In step 2), the unsaturated carboxylic acid monomer is one or more of methacrylic acid or acrylic acid.

4. The preparation method according to claim 1, characterized in that, In step 2), the unsaturated polyether macromonomer is one or more of isopentenyl polyoxyethylene ether or allyl polyoxyethylene ether, and the molecular weight of the unsaturated polyether macromonomer is 1000~3000.

5. The preparation method according to claim 1, characterized in that, In step 2), the unsaturated sulfonic acid monomer is one or more of sodium vinyl sulfonate or sodium methpropylene sulfonate.

6. The preparation method according to claim 1, characterized in that, The preparation method includes the following steps: 1) Add deionized water to the reaction vessel and raise the temperature; 2) Add unsaturated carboxylic acid monomer, unsaturated polyether macromonomer, unsaturated sulfonic acid monomer, viscosity reducing monomer and foam stabilizing functional monomer to the reaction vessel, and stir until completely dissolved; 3) Add oxidizing and reducing agents dropwise to initiate a free radical reaction; 4) After the reaction is complete, cool down and adjust the pH value to 6-7 to obtain the comb-type polymerized viscosity-reducing air-entraining agent; The foam-stabilizing monomer is one or more of acrylamide or allyl dodecyl polyether; the viscosity-reducing monomer is one or more of methyl methacrylate, vinyl oleate, lauryl methacrylate or vinyl stearate.

7. The preparation method according to claim 1, characterized in that, In step 3), the reaction temperature of the free radical reaction is 40~60℃, including a dropwise reaction stage and a heat preservation reaction stage. The dropwise reaction stage lasts for 2~3 hours, and the heat preservation reaction stage lasts for 3~4 hours.

8. The preparation method according to claim 1 or 6, characterized in that, In step 2), the mass ratio of the unsaturated carboxylic acid monomer, unsaturated polyether macromonomer, unsaturated sulfonic acid monomer, viscosity-reducing monomer, and foam-stabilizing monomer is 100~120∶420~480∶65~80∶0~50∶0~60.

9. A comb-type polymerized viscosity-reducing air-entraining agent prepared by the preparation method according to any one of claims 1-8.

10. The application of a comb-type polymeric viscosity-reducing air-entraining agent as described in claim 9 in concrete.